Seed anatomy and germination of Phoenix roebelenii O'Brien (Arecaceae) - Iossi,Emerson (2006)
The objective of this study was to investigate the morphology, anatomy and germination behaviour of Phoenix roebelenii seeds. Biometric data were obtained by measuring 100 seeds extracted from recently harvested fruits and air-dried for one day. Four replications of 50 seeds each were previously treated with Vitavax-Thiran and then put to germinate in Sphagnum sp. in plastic trays at room temperature. Morphological details of the seeds were documented with the help of a scanning electronic microscope and then drawings were made with the help of a clear camera coupled to a stereomicroscope. Permanent lamina containing embryo sections were prepared to study its anatomy. The mean dimensions of the seeds were: length of 10.32mm, width of 5.21mm and thickness of 3.91mm. The weight of one thousand seeds was of 151.1g and the mean number of units.kg-1 was 6,600. Germination started between 27 and 58 days after sowing. The seeds are of the albuminous type, the endosperm is hard and the embryo (which is not clearly differentiated) occupies a lateral and peripheral position. During seed germination, seedling protrusion begins with the opening of an operculum, through which the cotyledon petiole is emitted with the embryonic axis at its tip. The portion of the cotyledon petiole that remains inside the seeds acts as a haustorium for the absorption of nutrients from the endosperm. The plumule emerges through a rift in the posterior part of the cotyledon. Secondary roots are observed to grow from the anterior part of the primary root.